Stock Market Reactions to Auto Manufacturers' Environmental Failures. (December 2018) - Wood, Lincoln C.; Wang, Jason X.; Duong, Linh N. K.; Reiners, Torsten; Smith, Rikki
The automotive sector must meet strict regulations to increase mobility while reducing emissions to demonstrate environmental stewardship. Trust in the promise of a sustainable Fahrvergnügen was broken with recent scandals like Dieselgate denting the confidence of regulators and consumers. Overpromising on sustainable innovative technology resulted in unethical behavior, deceit, and failure to meet promised standards. We consider to what extent societal disapproval was evident in the stock market reaction to these events. We sampled 41 announcements (1984 to 2016) and observed a mean stock market reaction of -1.01%. There was no difference in the stock reaction in firms failing governmental vs. voluntary standards and more negative reactions for events following Dieselgate or when compensation was offered. The severity of the reaction to unethical misuse of environmental credentials should encourage maintaining promised environmental performances as a macromarketing strategy.